MRI Features of the Vomeronasal Organ in Dogs (Canis Familiaris) - Dzięcioł, Michał; Podgórski, Przemysław; Stańczyk, Ewa; Szumny, Antoni; Woszczyło, Martyna; Pieczewska, Barbara; Niżański, Wojciech; Nicpoń, Józef; Wrzosek, Marcin Adam (Frontiers in Veterinary Science, 2020)
The vomeronasal organ (VNO, Jacobson's organ) according to current knowledge is the structure responsible for semiochemical signal detection. In dogs and other mammals, it is localized close to the vomer and nasal bones. Although there are reports describing the anatomy and histology of this structure, there are no available reports assessing this organ in live individuals by direct visualization. The aim of this study was twofold: (1) preparation and optimization of a protocol for magnetic resonance imaging (MRI) examination of the VNO in a cadaver study with its precise visualization and localization, and (2) characterization of the physiological VNO image features in an MRI of live dogs. The first part of the study was performed on 10 beagle cadavers, the second on 8 live beagle dogs. For the VNO visualization, a 1.5T MRI (Philips® Ingenia) scanner and 20-channel digital head-neck spine coil were used (Philips®, Holland). The cadaver study allowed confirmation of the organ's localization by the application of an MRI contrast agent (gadolinium), through the external entrance of the VNO canal. Accurate delineation of the VNO was obtained using a high-resolution submillimeter three-dimensional T1-FFE 3D sequence. Imaging of the VNO in 8 living dogs allowed description of the MRI physiological features and direct evaluation of its shape and size. The results obtained demonstrate the ability to visualize the VNO in vivo and to evaluate its structure in dogs.